Dietary electrolytes and thermal conditioning: minimizing heat stress in broilers - Garcia Neto, Manoel [UNESP]; Minello, Maria Clara da Silva [UNESP]; Ponsano, Elisa Helena Giglio [UNESP]; Almeida, Marcel Alessandro de [UNESP]; Faria Júnior, Max José de Araújo [UNESP]; Pinto, Marcos Franke [UNESP] (My University, 2013)
In tropical climates the heat is one of the major constraints to production of broilers and is responsible for inducing a high mortality, especially in the finishing phase. Thus, the objective of this study was to compare the thermal conditioning early (TC) and feed formulation using dietary electrolytes (DE). Therefore, the electrolyte balance of K+Na-Cl was set at 350 mEq/kg and electrolyte ratio (K+Cl)/Na) in the 3:1 program PPFR (http://www.fmva.unesp.br/ppfr). A total of 300 Cobb 500 1-dold male broiler chicks was randomly allocated to 24 floor pens with six replicates per treatment in a 2x2 factorial arrangement (with and without TC and with and without DE). Dietary treatments consisted: (T1) a traditional diet without TC; (T2) traditional diet with TC; (T3) with the application of dietary electrolyte and without TC and (T4) application of dietary electrolyte with TC. The thermal conditioning was conducted at 5 d of age (36°C for 24 h), only half of the batch (150 birds). After this period, all birds were transferred to boxes of 1.5 x3m (12 birds / box), with wood shavings reused as litter. Chicks were exposed to acute stress (36°C) for 8 h at the age 36, in all treatments, being electronically monitored the temperature and humidity of the microclimate of the birds. Feed and water were provided ad libitum, even during periods of stress. Were measured performance data (weight gain, feed intake and feed conversion) and mortality rate. The early thermal conditioning (T2) and effect of dietary electrolytes (T3) were effective to minimize the mortality of broilers subjected to acute heat stress with a significant difference (P<0.05), without prejudice on broiler performance. The results also showed that there was a more favorable effect when applied dietary electrolytes and thermal conditioning simultaneously (treatment T4). However, for the treatment none of these strategies has been applied (T1), the mortality rate was 83% over that in which they were applied (T4). It was concluded from this study that both techniques: the thermal conditioning early as the dietary electrolytes are efficacious in minimize the damaging effects caused by heat broiler.
Keywords: Acute stress; Cation-anion balance; Dietary cation-anion; Electrolyte diet; Heat stress